Kebijakan Hukum Pengaturan Praktek Santet dalam Hukum Pidana Indonesia - Badri, Mhd.; Sumaidi, Sumaidi; Iswanto, Reza (Wajah Hukum, 2025)
The phenomenon of black magic is still a topic of discussion in Indonesia and is believed to still exist, even though it is regulated in Article 252 of Law No. 1 of 2023 concerning the Criminal Code. However, there are no specific procedural legal regulations governing the crime of black magic, making it difficult to reveal it based on the old Criminal Procedure Code. The research method applied in this study is the legislative approach, with an activity plan that lasts for six months. The scope or object of study in this study is the criminal law policy related to the regulation of black magic practices in Criminal Law in Indonesia. The main legal sources used include primary legal materials such as Law Number 1 of 2023 concerning the Criminal Code, secondary legal materials consisting of books and articles by legal experts and tertiary legal materials used include encyclopedias and other publications relevant to this research. The location of this research is Indonesia so that the data collection technique used is document study, while the analysis technique applied is qualitative analysis. The results of this study are that the current legal policy for regulating black magic practices is that the regulation regarding this matter has been regulated in material law, namely Article 252 of Law Number 1 of 2023 concerning the Criminal Code. Furthermore, the legal policy regarding the regulation of black magic practices in the future requires formal law or procedural law that regulates investigation and inquiry procedures. Thus, this black magic case can be enforced and the perpetrators can be subject to appropriate criminal sanctions.